Liquid crystals in waveguides for tuning and sensing - Neyts, Kristiaan; Decort, Wout; Azarinia, Hamidreza; Vanbrabant, Pieter; James, Richard; Beeckman, Jeroen (Photonics Letters of Poland, 2011)
The orientation of liquid crystal in the neighborhood of an optical waveguide determines the propagation speed and the losses in the waveguide. This principle can be used for tuning the resonance frequency of a ring resonator or for sensing the presence of molecules at the interface between water and liquid crystal. In this work, experimental evidence and qualitative explanations are provided for these two cases. Full text: PDF References: B. Maune, R. Lawson, C. Gunn, A. Scherer, L. Dalton, "Electrically tunable ring resonators incorporating nematic liquid crystals as cladding layers", Appl. Phys. Lett. 83, 4689 (2003). [CrossRef] W. De Cort et al., "Tuning silicon-on-insulator ring resonators with in-plane switching liquid crystals", J. Opt. Soc. Am. B 28, 79 (2011). [CrossRef] C. Veilleux, R.J. Black, J. Lapierre, L.W. Reeves, "Nematic liquid crystal clad tapered optical fiber with temperature sensing properties", J. Appl. Phys. 67, 6648 (1990). [CrossRef] A. Di Falco,G. Assanto, "Tunable wavelength-selective add-drop in liquid crystals on a silicon microresonator", Opt. Comm. 279, 210 (2007). [CrossRef] J. Beeckman et al., "Calculation of Fully Anisotropic Liquid Crystal Waveguide Modes", J. Lightwave Techn. 27, 3812 (2009). [CrossRef] Y. Xu, M.A. Uddin, P.S. Chung, H.P. Chan, "Polymer planar waveguide device using inverted channel structure with upper liquid crystal cladding", Opt. Exp. 17, 7837 (2009). [CrossRef] H. Desmet, K. Neyts, R. Baets, Integr. Opt. Silicon Photon. Photon. Integr. Circ. 6183, Z1831, 480 (2006). W. De Cort et al., "Tuning of silicon-on-insulator ring resonators with liquid crystal cladding using the longitudinal field component", Opt. Lett. 34, 2054 (2009).[CrossRef] H. Azarinia et al., "Orientation of nematic liquid crystal in open glass microstructures", J. Appl. Phys. 106, 063101 (2009). [CrossRef] V.K. Gupta, J.J. Skaife, T.B. Dubrovsky, N.L. Abbott, "Optical Amplification of Ligand-Receptor Binding Using Liquid Crystals", Science 279, 2077 (1998). [CrossRef] R. James, E. Willman, F.A. Fernandez, S.E. Day, "Computer Modeling of Liquid Crystal Hydrodynamics", IEEE Trans. Magnet. 44, 814 (2008). [CrossRef] F.A. Fernandez, S.E. Day, P. Trwoga, H.F. Deng, R. James, "Three-Dimensional Modelling of Liquid Crystal Display Cells using Finite Elements", Mol. Cryst. Liq. Cryst. 375, 291 (2002). [CrossRef]